Children's Position as a Result of Sirri Marriage Under Islamic and Positive Law in Indonesia - ., Muslim; Kurniati, Herlina (KnE Social Sciences, 2024)
Although registering a marriage does not determine its validity in Islam, unregistered marriages in Indonesia cause children to be unregistered by state law, which is known as a Sirri marriage. As a result, legally, Sirri marriages have a position and effect on a child’s status and position. In terms of the issues raised in this article, how do children affected by Sirri marriages fare under Islamic and positive law in Indonesia? Furthermore, the purpose of research in this article is to analyze position of children affected by Sirri marriages fare under Islamic and positive law in Indonesia. The research method used, emphasizes legal normative views of the type of research (library research), then analyzed using descriptive analytical method, to provide data that is comprehensive about the people, the state, or the symptoms of the other. The study’s findings show that children born from legal marriages under Islamic law and legal marriages under law are children born from legal weddings under Islamic law and following the procedures of Article 2 paragraph 1 and paragraph 2 of Law No. 1 of 1974. A kid born of a marriage that is valid in Islamic law and does not in the outside procedure in article 2 paragraph 2 is a child born of a marriage that is valid in Islamic law and does in the outside procedure. However, the status of Sirri marriage cannot be legally acknowledged because it is not recorded from the administrative side of unregistered marriages as stated in Article 2 paragraph (2) of Law No. 1 of 1974. Second, the legislation because of Sirri marriage to the position of children is to make the status and position of a kid unacknowledged if the child was born before the marriage of both parents and is registered, legally recognized, and recorded. Keywords: status of children due to Sirri marriage, Islamic Law, positive law In Indonesia